Shifting focus from bacteria to host neutrophil extracellular traps of biodegradable pure Zn to combat implant centered infection - Feng Peng; Juning Xie; Haiming Liu; Yufeng Zheng; Xin Qian; Ruixiang Zhou; Hua Zhong; Yu Zhang; Mei Li (Bioactive Materials, 2023)
The widespread use of orthopedic implants to support or replace bones is increasingly threatened by the risk of incurable bacterial infections, impenetrable microbial biofilms, and irreversible antibiotic resistance. In the past, the development of anti-infective biomaterials focused solely on direct antibacterial properties while ignoring the host's immune response. Inspired by the clearance of infection by the innate neutrophil response and participation in anti-infectious immunity of Zn ions, we report an innovative neutrophil extracellular traps (NETs) strategy, induced by biodegradable pure Zn, which achieved therapeutic efficacy toward biomaterial-related infections. Our in vitro and in vivo data showed that pure Zn was favorable for NETs formation by promoting the release of DNA fibers and granule proteins in a reactive oxygen species (ROS)-dependent manner, thereby retraining and degrading bacteria with an efficiency of up to 99.5%. Transcriptome analysis revealed that cytoskeletal rearrangement and toll-like receptor (TLR) signaling pathway were also involved in Zn-induced NETs formation. Furthermore, the in vivo results of a Staphylococcus aureus (S. aureus)-infected rat model verified that pure Zn potentiated the bactericidal capability of neutrophils around implants, and promoted osseointegration in S. aureus-infected rat femurs. This antibacterial immunity concept lays a foundation for the development of other antibacterial biomaterials and holds great promise for treating orthopedic infections.